“Plan de Marketing para la empresa Forbet (apuestas deportivas) de la ciudad de Catamayo, provincia de Loja” - Minga Curipoma, Ronny Jorge (2025)
The main objective of this research was to develop a marketing plan for the company Forbet, a sports betting house located in the city of Catamayo, province of Loja. To this end, a detailed internal and external analysis of the company was carried out, in order to identify its strengths, weaknesses, opportunities and threats within the market. As part of the study, digital surveys were conducted with a sample of 120 people, including clients and non- customers of the brand, as well as an interview with the company manager. The results showed that 79.2% of Forbet users are men and 20.8% are women, with a greater concentration of clients in the 22 to 26 year-old range (45.8%). Most customers have been users for relatively short periods (6 to 12 months), which highlights the need to implement loyalty strategies. In terms of service quality, only 10.8% of those surveyed stated that they received technical support constantly, while 50% indicated that they received it rarely, evidencing a key opportunity for improvement in customer service in the company. A relevant competitive factor identified was speed of payments, preferred by 56.7% of respondents. Regarding the dissemination of the brand, 32.5% of those surveyed learned about Forbet through recommendations from friends or family and 30% through social networks, mainly Facebook, making it necessary to implement marketing strategies. However, the company faces significant competition, with 53% of respondents also using Ecuabet and 45% using Bet365. Based on these findings, various marketing strategies were proposed to improve Forbet's competitiveness. Among the proposals, the holding of weekly raffles stands out (88.3% preference among those surveyed), the implementation of a PESS championship as a recreational activity (76.7%) and giving away t-shirts from different soccer teams as a promotional incentive (49.2%). It is concluded that Forbet has competitive advantages such as fast payments and accessible schedules, but it must optimize its customer service, strengthen its loyalty strategies and improve its positioning through greater investment in advertising and promotion, especially digital. The implementation of the proposed marketing plan will allow Forbet to consolidate itself as a benchmark in the sports betting market in Catamayo, offering a more attractive experience, guaranteeing its sustainability in a highly competitive environment and positioning itself as pioneers in the national market.